Analisis Penilaian Tingkat Kesehatan Koperasi Syariah Dalam Upaya Meningkatkan Kinerja Di Koperasi As-Sakinah Sidoarjo - Siti Masula; Renny Oktafia (ITB AAS INDONESIA Surakarta, 2021)
Financial Institutions are an important part in economic development in Indonesia, the existence of cooperatives is expected to realize the welfare of the community with the principle of helping. Considering, most indonesians are majority Muslim. However, in practice, cooperatives that develop today still use conventional systems, where in the view of the public there is still usury and is considered not in accordance with sharia principles. To make the operational principles of cooperatives in accordance with sharia principles, a Sharia Cooperative or Baitul Mal Wa Tamwil (BMT) was formed. The development of Sharia Cooperatives is very good in Indonesia. Based on data from the Ministry of Cooperatives and SMEs, the number of Sharia Cooperative business units reached 150,223 units with a total of 1.4 million members. The capital alone reached Rp.968 billion and the outside capital rp.3.9 trillion with a business volume of Rp.5.2 trillion. The purpose of this study is to find out the assessment of health level as well as the impact of health level assessment in an effort to improve the performance of Sharia Cooperative As-Sakinah Sidoarjo. This study uses qualitative descriptive method with case study approach that aims to gain in-depth knowledge related to events or problems that occur. The results of this study show that overall, the level of health of Cooperative As-Sakinah Sidoarjo can be said to be good even though there are still problems or obstacles that occur. The assessment of the level of health of cooperatives is able to improve the performance of cooperatives to be better and continue to improve in order to improve the development of cooperatives in the future.